PENATALAKSANAAN EDUKASI PERSONAL HYGIENE UNTUK MENINGKATKAN PENGETAHUAN IBU HAMIL - Erna Kasim; Nurkamiden, Ayu; Magdalena Limbong; Ekayanti Ahmad; Andi Tenriola Fitri (Jurnal Kesehatan Panrita Husada, 2024)
Knowledgepersonal hygiene in pregnant women is very important because good knowledge can improve health in pregnant women themselves. Research purposes:. This study aims to identify the management of education aboutpersonal hygiene in pregnant women. Method: In this study the methods used were interviews and observation. Results:After conducting a case study between Mrs "N" and Mrs "M" there was no gap, this was because the two subjects had knowledge above 50%, which meant that the knowledge of the two case study subjects was good. Conclusion:Based on the basis of case theory and discussion, it can be concluded that Educational ManagementPersonal Hygiene To increase the knowledge of pregnant women, which is good with a value above 50%. Suggestion:It is recommended for writers to be a reference to gain knowledge and deepen and broaden insights in preparing scientific paper proposals.